PENGARUH IDEALISME AKUNTAN TERHADAP PENILAIAN PERILAKU AKUNTANSI KREATIF - Ikraam, Ikraam; Hadli, Hadli (Jurnal Manajemen, 2019)
The main purpose of this study is to analyze the influence of idealism on the assessment of creative accounting behavior. This study uses idealism and assessment of creative accounting behavior as research variables. The research variables are taken from the theory of individual moral philosophy. This study uses 125 accountants as a sample collected by the census method. Based on the research findings, the accountant idealism variable has a significant impact and has a negative relationship from the assessment of accounting creative practices, in other words it is stated that the higher the idealism held by accountants, the creative accounting practices will be judged as unethical by accountants.